Text companion - Stata Corporation (Belmont, Calif)
A student version of the Stata data analysis and graphics program for learning how to do statistics on a DOS-based computer. This "text companion" subset of StataQuest is designed to accompany virtually any statistics textbook
Keywords: Social sciences; Social sciences